A novel means of comparing the bioequivalence of two formulations of tripotassium dicitrato bismuthate (De-Noltab). Issue 756 (October 1988) - Coghill, S. B.; Shepherd, A. N.
Abstract : Tripotassium dicitrato-bismuthate (TDB) has a topical action in the upper gastrointestinal tract. Absorption is minimal and the blood levels are therefore irrelevant to the assessment of bioavailability. TDB is however detectable in the stomach and duodenum by conventional electron microscopy. Following oral administration of two different formulations of TDB tables to patients attending a gastroscopy clinic, duodenal biopsies were obtained and examined by electron microscopy. The amount of electron dense drug precipitate was quantified. No difference could be detected between the two formulations.